Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s00424-017-1999-6
|View full text |Cite
|
Sign up to set email alerts
|

Salt-induced Na+/K+-ATPase-α/β expression involves soluble adenylyl cyclase in endothelial cells

Abstract: High dietary salt intake may lead to vascular stiffness, which predicts cardiovascular diseases such as heart failure, and myocardial and cerebral infarctions as well as renal impairment. The vascular endothelium is a primary target for deleterious salt effects leading to dysfunction and endothelial stiffness. We hypothesize that the Ca- and bicarbonate-activated soluble adenylyl cyclase (sAC) contributes to Na/K-ATPase expression regulation in vascular endothelial cells and is an important regulator of endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…In the vascular endothelium, the role that the sAC-cAMP axis plays in Na + /K + -ATPase regulation has been demonstrated, as the inhibition of sAC (KH7 and interfering RNA) significantly decreases the mRNA and protein levels of Na + /K + -ATPase [ 84 ]. A recent study confirmed that the sAC-dependent regulation of Na + /K + -ATPase in the vascular endothelium plays an important role in endothelial stiffness [ 83 ].…”
Section: Functional Role Of Sac In Different Cellular Compartmentsmentioning
confidence: 88%
See 1 more Smart Citation
“…In the vascular endothelium, the role that the sAC-cAMP axis plays in Na + /K + -ATPase regulation has been demonstrated, as the inhibition of sAC (KH7 and interfering RNA) significantly decreases the mRNA and protein levels of Na + /K + -ATPase [ 84 ]. A recent study confirmed that the sAC-dependent regulation of Na + /K + -ATPase in the vascular endothelium plays an important role in endothelial stiffness [ 83 ].…”
Section: Functional Role Of Sac In Different Cellular Compartmentsmentioning
confidence: 88%
“…sAC, in a PKA-dependent manner, is especially involved in corticotropin-releasing hormone-mediated CREB phosphorylation and c-fos (endogenous CREB target) induction in hippocampal neuronal cells [ 82 ]. A recent study demonstrated that sAC contributes to the regulation of CREB-mediated Na + /K + -ATPase expression in the vascular endothelium and is an important regulator of endothelial stiffness [ 83 , 84 ]. Besides promoting CREB activity, sAC also regulates several other transcription factors.…”
Section: Functional Role Of Sac In Different Cellular Compartmentsmentioning
confidence: 99%
“…The consumption of salt amounts that exceed the buffer capacity of the glycocalyx is a factor that contributes to its destruction and to the movement of sodium from the vascular bed into the intercellular space [9,10]. It was shown that the expression of Na + /K + -ATPase and the related endothelial stiffness increase under a high salt load [15]. The use of erythrocyte models to estimate individual salt sensitivity based on the sodium buffer capacity of the glycocalyx and of osmotic fragility based on the activity of sodium transporters is justified by the similarity between the endothelium and erythrocytes in relation to sodium transporters [27] and by the functional similarity of their glycocalyces [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Na + /K + -ATPase expression in the vascular endothelium is an important regulator of endothelial stiffness under an excessive salt load [15].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been noted that the vascular endothelium is an important ‘mechano-sensor’ transducing hemodynamic signals which may result in flow-induced conversion of endothelial cells into an elongated arterial phenotype as well as in functional and structural changes of the overall arterial wall [20, 23]. Of note, vascular maladaptations including endothelial cell stiffening, disturbed endothelial barrier function and reduced nitric oxide (NO) production [24, 25] as well as the development of atherosclerotic lesions and plaque formation is mainly found in regions with disturbed flow which increases the secretion of pro-inflammatory molecules and most likely alters miRNA expression [26, 27]. By contrast, these deleterious changes are mostly absent from regions with constant laminar flow [26].…”
Section: Introductionmentioning
confidence: 99%